Functional Heterogeneity in Superorganisms: Emerging Trends and Concepts. (4th November 2020) - O'Shea-Wheller, Thomas A; Hunt, Edmund R; Sasaki, Takao
Abstract: Social insects are biological benchmarks of self-organization and decentralized control. Their integrated yet accessible nature makes them ideal models for the investigation of complex social network interactions, and the mechanisms that shape emergent group capabilities. Increasingly, interindividual heterogeneity, and the functional role that it may play, is seen as an important facet of colonies' social architecture. Insect superorganisms present powerful model systems for the elucidation of conserved trends in biology, through the strong and consistent analogies that they display with multicellular organisms. As such, research relating to the benefits and constraints of heterogeneity in behavior, morphology, phenotypic plasticity, and colony genotype provides insight into the underpinnings of emergent collective phenomena, with rich potential for future exploration. Here, we review recent advances and trends in the understanding of functional heterogeneity within social insects. We highlight the scope for fundamental advances in biological knowledge, and the opportunity for emerging concepts to be verified and expanded upon, with the aid of bioinspired engineering in swarm robotics, and computational task allocation.